Hubungan menyikat gigi pada malam hari dengan karies gigi pada anak usia 10-12 tahun - Siti Annisa Putri; Herry Imran (DAPU Aceh Publishing, 2025)
Brushing teeth at night is an important habit in maintaining dental hygiene and preventing caries and can clean food debris attached to the teeth so that plaque formation during sleep can be inhibited. However, this habit is still low practiced by children. Dental caries is one of the most common dental health problems, especially in school-age children. This study aims to determine the relationship between the habit of brushing teeth at night with the incidence of dental caries in children aged 10-12 years in Gampong Laksana, Kuta Alam District, Banda Aceh City. This study used an analytic design with cross-sectional technique. The sample amounted to 38 children aged 10-12 years who were selected using proportional sampling technique. Data were collected through questionnaires and direct examination using the DMF-T/def-t index. Analysis was done univariately and bivariately using the Chi-square test. This study was conducted on May 1-3, 2025. The results showed that the majority of children had poor nighttime brushing habits or did not brush their teeth at night as much as 71.1% and 28.9% of children had very high caries levels. Statistical test results showed a significant relationship between nighttime brushing habits and the incidence of dental caries (p-value = 0.001). There is a significant relationship between brushing teeth at night and the incidence of dental caries in children aged 10-12 years.